Pengaruh Media Sosial Whatsapp Terhadap Hasil Belajar Mata Pelajaran Ekonomi Siswa Kelas X SMAS Purnama Jakarta - Nuramalia, Ainun; Adawiyah, Robiatul; Taufik, Taufik (Neolectura, 2024)
The aim of this research is to determine the influence of WhatsApp social media on learning outcomes in economics subjects. By using a quantitative approach method, the sampling technique in this research uses nonprobability sampling with a sampling technique using saturated sampling, where the number of samples is the same as the population. The number of samples used was 48 students. After conducting research according to the title